1994
DOI: 10.1182/blood.v83.6.1460.1460
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the Ki-67-associated proliferative antigen in aggressive non-Hodgkin's lymphomas: a prospective Southwest Oncology Group trial

Abstract: The growth fraction of tumors from patients with non-Hodgkin's lymphomas (NHL) has been shown to correlate with survival in retrospective studies. The growth fraction can be evaluated using immunohistochemical techniques employing the Ki-67 monoclonal antibody (MoAb) that marks a nuclear protein present in cycling cells. The purpose of this study was to evaluate the clinical utility of the Ki-67 MoAb for predicting survival. Using a prospective trial design in a multi-institutional cooperative trials group, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
73
3
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(84 citation statements)
references
References 0 publications
5
73
3
3
Order By: Relevance
“…Ki‐67 index, cMyc index, starry sky pattern, and necrosis are considered to be correlated immunohistochemical and histopathological findings, and all of them are associated with proliferation activity of tumors. High Ki‐67 index and high cMyc index reflecting cMYC rearrangement were reported to be poor prognostic parameters . The predictive value of Ki‐67 index was reported in the pre‐rituximab era .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ki‐67 index, cMyc index, starry sky pattern, and necrosis are considered to be correlated immunohistochemical and histopathological findings, and all of them are associated with proliferation activity of tumors. High Ki‐67 index and high cMyc index reflecting cMYC rearrangement were reported to be poor prognostic parameters . The predictive value of Ki‐67 index was reported in the pre‐rituximab era .…”
Section: Discussionmentioning
confidence: 97%
“…Immunohistochemical expression of Bcl‐2 and CD5 has been reported to be associated with an unfavorable prognosis; expression of Bcl‐6 and CD10 are associated with a favorable prognosis. High Ki‐67 index has also been reported to be a poor prognostic parameter. However, these results were obtained mainly in the pre‐rituximab era.…”
mentioning
confidence: 99%
“…Furthermore, similar to our findings, they reported that the histological grade did not predict the outcome. (5) Miller et al (6) and Martin et al (7) found that the MIB-1 labeling index correlated with OS but not with PFS. However, in the study of Martin et al, (7) significance was not detected by the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…(5) Miller et al (6) and Martin et al (7) found that the MIB-1 labeling index correlated with OS but not with PFS. However, in the study of Martin et al, (7) significance was not detected by the multivariate analysis. Wang et al (8) reported that patients with low-grade FL and a high proliferation index determined by MIB-1 labeling index tended to have a shorter OS (P = 0.087) than those with a low proliferation index.…”
Section: Discussionmentioning
confidence: 99%
“…The PI is known to be an important predictor of outcome in diffuse large B cell lymphoma and MCL (Miller et al, 1994;Schaffel et al, 2010) as well as solid tumours, such as breast and prostate cancer (Scholzen & Gerdes, 2000), but its role in FL is not well established. A few previous studies have addressed this question in somewhat different ways (Wang et al, 2005;Klapper et al, 2007;Koster et al, 2007).…”
Section: Discussionmentioning
confidence: 99%